PERLINDUNGAN HUKUM TERHADAP HAK ORANG DENGAN HIV DALAM PELAYANAN KESEHATAN: STUDI DI PUSKESMAS REJOSARI KOTA PEKANBARU - Silvia Permatasari; Yeni Triana; Irawan Harahap (Jurnal Ilmiah Advokasi, 2025)
This study aims to analyze the legal protection of the rights of People Living with HIV (PLHIV) in health services at Rejosari Community Health Center (Puskesmas) in Pekanbaru City, to identify obstacles in its implementation, and to formulate possible improvement measures. This research employs a sociological legal approach with an empirical method. The data were collected from primary, secondary, and tertiary legal materials, supported by interviews and field observations. The findings indicate that, normatively, the legal protection of PLHIV is regulated under Law Number 17 of 2023 on Health, Law Number 39 of 1999 on Human Rights, and Minister of Health Regulation Number 23 of 2022 concerning the Prevention and Control of HIV, AIDS, and Sexually Transmitted Infections. These regulations guarantee the right to non-discriminatory health services, confidentiality of medical status, and access to treatment. However, the implementation at the primary health care level has not been fully optimal. The identified obstacles include limited understanding among health personnel regarding legal protection aspects, persistent social stigma, and concerns about maintaining the confidentiality of patients’ medical data. Efforts undertaken to address these challenges include regulatory socialization, training on standard operating procedures for HIV management, and strengthening commitments to the principles of non-discrimination and medical confidentiality. This study underscores the importance of harmonizing legal norms and health service practices to ensure effective and sustainable protection of the rights of PLHIV.Keywords: legal protection; people living with HIV; health services; human rights; community health center